Improvement of accuracy for the determination of vitamin A in infant formula by isotope dilution-liquid chromatography/tandem mass spectrometry - Lim, Young Ok; Kim, Byungjoo; Ahn, Seonghee; Kim, Jeongkwon (Food chemistry, 2011)
► ID-LC/MS method for the accurate determination of vitamin A in infant formula. ► Sample preparation method for preventing oxidative degradation of vitamin A. ► Measurement uncertainty is improved to be less than 1%. ► Presentation of method validation data. Analysis of vitamin A in food has been an intricate subject due to its labile properties. In this study, an isotope dilution-liquid chromatography/mass spectrometric (ID-LC/MS) method was established as a candidate reference method for the accurate determination of vitamin A in infant formula. We found that the oxidative degradation of vitamin A in sample preparation processes is a key fact that hampers reliability of measurement results. Therefore, sample preparation processes were carefully designed to minimise oxidative degradation of vitamin A by preventing sample from exposure to air. Similar cautions were applied for the preparation of calibration solutions. Both within-day repeatability and among-day reproducibility tests of the ID-LC/MS method showed less than 1.0% of relative standard deviation, and the measurement uncertainty by this method is estimated to be less than 1.0%. The newly designed method showed greatly improved performance compared to methods reported in other literatures.